Mechanisms of coronary microvascular tone regulation: aging and sex differences - Fees, Alexander Jacob (Kansas State University, 2018)
The coronary microcirculation is the principle site of blood flow control and myocardium oxygen delivery within the coronary artery tree. Coronary arteriole tone is determined by three major endothelium derived vasoactive substances: endothelin, nitric oxide (NO), and reactive oxygen species (ROS). The effects of these substances change with aging and differ between sexes. Endothelin-1 (ET-1), the primary endothelin isoform in the coronary circulation, acts on smooth muscle receptors endothelin-A (ET[subscript A]) and endothelin-B (ET[subscript B]) to induce vascular smooth muscle (VSM) contraction and vasoconstriction. Whereas ET-1 activation of the ET[subscript B] receptor on the endothelium initiates a cascade of events leading to NO production via endothelium derived NO synthase (eNOS) enzyme activation and VSM relaxation. Aged males maintain ET[subscript A] receptor expression and higher levels of vasoconstriction than do age-matched females. High levels of ET[subscript A] receptor activity are associated with hypertension, myocardial infarction, coronary artery spasm, atherosclerosis, and finally heart failure (HF). Additionally, NO can displace ET-1 from the VSM ET[subscript A] and ET[subscript B] receptors. Thus, with reduced eNOS activity and decreased NO production, there is a simultaneous loss of vasodilatory capacity and increase in vasoconstrictive capacity. In both rodent and human models aged males and females ROS production increases with age. ROS, such as superoxide, scavenge NO, decreasing its bioavailability and producing peroxynitrite. Peroxynitrite is a potent reactive nitrogen species that leads to endothelial cell apoptosis and eNOS enzyme dissociation, potentiating superoxide production and NO reduction. It has been shown that the reduction in NO bioavailability may be a primary mechanism of coronary artery disease. However, the ROS hydrogen peroxide, also increased with aging, produces a potent vasodilatory effect in the coronary microcirculation and seems to be one mechanism that buffers the loss of NO-induced vasodilation. In postmenopausal women diminished estrogen levels further reduce eNOS production of NO. Males, however, tend to experience decrements in arteriole function a decade before women and estrogen may be one mechanism preserving vascular health into middle age that separates the chronology of coronary artery disease between sexes. Determining the mechanisms of disease onset that accompany the aging process will provide insight into potential therapies to preserve endothelium dependent dilation with aging such as exercise, dietary NO supplementation, and increased dietary anti-oxidant consumption.
Keywords: Coronary arterioles; Female; EndothelinAging